Interatrial block, P terminal force or fragmented QRS do not predict new-onset atrial fibrillation in patients with severe chronic kidney disease - Tapio Hellman; Markus Hakamäki; Roosa Lankinen; Niina Koivuviita; Jussi Pärkkä; Petri Kallio; Tuomas Kiviniemi; K. E. Juhani Airaksinen; Mikko J. Järvisalo; Kaj Metsärinne (BMC, 2022)
Background: The prevalence of left atrial enlargement (LAE) and fragmented QRS (fQRS) diagnosed using ECG criteria in patients with severe chronic kidney disease (CKD) is unknown. Furthermore, there is limited data on predicting new-onset atrial fibrillation (AF) with LAE or fQRS in this patient group. Methods: We enrolled 165 consecutive non-dialysis patients with CKD stage 4-5 without prior AF diagnosis between 2013 and 2017 in a prospective follow-up cohort study. LAE was defined as total P-wave duration >= 120ms in lead II >1 biphasic P-waves in leads II, III or aVF; or duration of terminal negative portion of P-wave >40ms or depth of terminal negative portion of P-wave >1mm in lead V-1 from a baseline ECG, respectively. fQRS was defined as the presence of a notched R or S wave or the presence of >= 1 additional R waves (R') or; in the presence of a wide QRS complex (>120ms), >2 notches in R or S waves in two contiguous leads corresponding to a myocardial region, respectively. Results: Mean age of the patients was 59 (SD 14) years, 56/165 (33.9%) were female and the mean estimated glomerular filtration rate was 12.8ml/min/1.73m(2). Altogether 29/165 (17.6%) patients were observed with new-onset AF within median follow-up of 3 [IQR 3, range 2-6] years. At baseline, 137/165 (83.0%) and 144/165 (87.3%) patients were observed with LAE and fQRS, respectively. Furthermore, LAE and fQRS co-existed in 121/165 (73.3%) patients. Neither findings were associated with the risk of new-onset AF within follow-up. Conclusion: The prevalence of LAE and fQRS at baseline in this study on CKD stage 4-5 patients not on dialysis was very high. However, LAE or fQRS failed to predict occurrence of new-onset AF in these patients.